Sistemas participativos de garantia :o caso da Associação de Agricultura Natural de Campinas (SP) e Região - muito além do controle - Thomson, Carolina Rios (2014)
This dissertation presents a brief historical and an overview of Participatory Guarantee Systems (PGSs) experiences worldwide and draws up a sociological analysis concerning the process of organic regulation in Brazil. It also contains a case study of a PGS based on the Natural Agriculture Association of Campinas and Region (ANC, by its acronym in Portuguese), located in the municipality of Campinas, state of São Paulo, Brazil. For the historical review, the methodology included literature review, interviews with key actors related to the Brazilian agroecological movement and documental analysis. For the case study, the techniques employed were participatory observation during the field research, analysis of ANC´s documents and interviews with ANC s producers, focused on both individual and organizational trajectories. The study revealed that the participation of Civil Society in the regulation of organic production in Brazil, especially through the agroecological movement, was the main reason for the brazilian legislation to become the first one that recognized PGSs in the same level as Third Party Certifiers. The case study revealed that the experiences exchange and the continuous members capacitation are the main advantages of ANC´s PGS. On the other hand, the major challenges were to overcome bureaucracy as well as direct and indirect costs in order to maintain the PGS´s activities.